Revealing local structural properties of an atomically thin MoSe2 surface using optical microscopy - Pan, Lin; Miao, Peng; Horneber, Anke; Meixner, Alfred J.; Adam, Pierre-Michel; Zhang, Dai (Beilstein Journal of Nanotechnology, 2022)
Using a triangular molybdenum diselenide (MoSe2) flake as surface-enhanced Raman spectroscopy (SERS) platform, we demonstrate the dependency of the Raman enhancement on laser beam polarization and local structure using copper phthalocyanine (CuPc) as probe. Second harmonic generation (SHG) and photoluminescence spectroscopy and microscopy are used to reveal the structural irregularities of the MoSe2 flake. The Raman enhancement in the focus of an azimuthally polarized beam, which possesses exclusively an in-plane electric field component is stronger than the enhancement by a focused radially polarized beam, where the out-of-plane electric field component dominates. This phenomenon indicates that the face-on oriented CuPc molecules strongly interact with the MoSe2 flake via charge transfer and dipole–dipole interaction. Furthermore, the Raman scattering maps on the irregular MoSe2 surface show a distinct correlation with the SHG and photoluminescence optical images, indicating the relationship between local structure and optical properties of the MoSe2 flake. These results contribute to understand the impacts of local structural properties on the Raman enhancement at the surface of the 2D transition-metal dichalcogenide.
Keywords: copper phthalocyanine; local structure; molybdenum diselenide; optical spectroscopy; surface-enhanced Raman spectroscopy

(untitled) - Bhimanapati, G. R.; Lin, Z.; Meunier, V.; Jung, Y.; Cha, J.; Das, S.; Xiao, D.; Son, Y.; Strano, M. S.; Cooper, V. R.; Liang, L.; Louie, S. G.; et al. (ACS Nano, 2015)

(untitled) - Zhao, M.; Ye, Z.; Suzuki, R.; Ye, Y.; Zhu, H.; Xiao, J.; Wang, Y.; Iwasa, Y.; Zhang, X. (Light: Sci. Appl., 2016)

(untitled) - Zhang, Y.; Chang, T.-R.; Zhou, B.; Cui, Y.-T.; Yan, H.; Liu, Z.; Schmitt, F.; Lee, J.; Moore, R.; Chen, Y.; Lin, H.; Jeng, H.-T.; et al. (Nat. Nanotechnol., 2014)

(untitled) - Yang, W.; Shang, J.; Wang, J.; Shen, X.; Cao, B.; Peimyoo, N.; Zou, C.; Chen, Y.; Wang, Y.; Cong, C.; Huang, W.; Yu, T. (Nano Lett., 2016)

(untitled) - Lopez-Sanchez, O.; Lembke, D.; Kayci, M.; Radenovic, A.; Kis, A. (Nat. Nanotechnol., 2013)

(untitled) - Jones, A. M.; Yu, H.; Ghimire, N. J.; Wu, S.; Aivazian, G.; Ross, J. S.; Zhao, B.; Yan, J.; Mandrus, D. G.; Xiao, D.; Yao, W.; Xu, X. (Nat. Nanotechnol., 2013)

(untitled) - Li, H.; Yin, Z.; He, Q.; Li, H.; Huang, X.; Lu, G.; Fam, D. W. H.; Tok, A. I. Y.; Zhang, Q.; Zhang, H. (Small, 2012)

(untitled) - Shen, Y. R. (Nature, 1989)

(untitled) - Huang, T.-X.; Cong, X.; Wu, S.-S.; Lin, K.-Q.; Yao, X.; He, Y.-H.; Wu, J.-B.; Bao, Y.-F.; Huang, S.-C.; Wang, X.; Tan, P.-H.; Ren, B. (Nat. Commun., 2019)

(untitled) - Lee, C.; Jeong, B. G.; Yun, S. J.; Lee, Y. H.; Lee, S. M.; Jeong, M. S. (ACS Nano, 2018)

(untitled) - Barja, S.; Wickenburg, S.; Liu, Z.-F.; Zhang, Y.; Ryu, H.; Ugeda, M. M.; Hussain, Z.; Shen, Z.-X.; Mo, S.-K.; Wong, E.; Salmeron, M. B.; Wang, F.; et al. (Nat. Phys., 2016)

(untitled) - Yin, X.; Ye, Z.; Chenet, D. A.; Ye, Y.; O’Brien, K.; Hone, J. C.; Zhang, X. (Science, 2014)

(untitled) - Chow, P. K.; Jacobs-Gedrim, R. B.; Gao, J.; Lu, T.-M.; Yu, B.; Terrones, H.; Koratkar, N. (ACS Nano, 2015)

(untitled) - Rosa, H. G.; Junpeng, L.; Gomes, L. C.; Rodrigues, M. J. L. F.; Haur, S. C.; Gomes, J. C. V. (Adv. Opt. Mater., 2018)

(untitled) - Sebait, R.; Biswas, C.; Song, B.; Seo, C.; Lee, Y. H. (ACS Nano, 2021)

(untitled) - Kim, M. S.; Yun, S. J.; Lee, Y.; Seo, C.; Han, G. H.; Kim, K. K.; Lee, Y. H.; Kim, J. (ACS Nano, 2016)

(untitled) - van der Zande, A. M.; Huang, P. Y.; Chenet, D. A.; Berkelbach, T. C.; You, Y.; Lee, G.-H.; Heinz, T. F.; Reichman, D. R.; Muller, D. A.; Hone, J. C. (Nat. Mater., 2013)

(untitled) - Lin, J.; Liang, L.; Ling, X.; Zhang, S.; Mao, N.; Zhang, N.; Sumpter, B. G.; Meunier, V.; Tong, L.; Zhang, J. (J. Am. Chem. Soc., 2015)

(untitled) - Nie, S.; Emory, S. R. (Science, 1997)

(untitled) - Stiles, P. L.; Dieringer, J. A.; Shah, N. C.; Van Duyne, R. P. (Annu. Rev. Anal. Chem., 2008)

(untitled) - Ling, X.; Fang, W.; Lee, Y.-H.; Araujo, P. T.; Zhang, X.; Rodriguez-Nieva, J. F.; Lin, Y.; Zhang, J.; Kong, J.; Dresselhaus, M. S. (Nano Lett., 2014)

(untitled) - Sun, L.; Hu, H.; Zhan, D.; Yan, J.; Liu, L.; Teguh, J. S.; Yeow, E. K. L.; Lee, P. S.; Shen, Z. (Small, 2014)

(untitled) - Zheng, Z.; Cong, S.; Gong, W.; Xuan, J.; Li, G.; Lu, W.; Geng, F.; Zhao, Z. (Nat. Commun., 2017)

(untitled) - Ling, X.; Wu, J.; Xu, W.; Zhang, J. (Small, 2012)

(untitled) - Huang, S.; Ling, X.; Liang, L.; Song, Y.; Fang, W.; Zhang, J.; Kong, J.; Meunier, V.; Dresselhaus, M. S. (Nano Lett., 2015)

(untitled) - Moore, D.; Jo, K.; Nguyen, C.; Lou, J.; Muratore, C.; Jariwala, D.; Glavin, N. R. (npj 2D Mater. Appl., 2020)

(untitled) - Tonndorf, P.; Schmidt, R.; Böttger, P.; Zhang, X.; Börner, J.; Liebig, A.; Albrecht, M.; Kloc, C.; Gordan, O.; Zahn, D. R. T.; Michaelis de Vasconcellos, S.; Bratschitsch, R. (Opt. Express, 2013)

(untitled) - Puretzky, A. A.; Liang, L.; Li, X.; Xiao, K.; Wang, K.; Mahjouri-Samani, M.; Basile, L.; Idrobo, J. C.; Sumpter, B. G.; Meunier, V.; Geohegan, D. B. (ACS Nano, 2015)

(untitled) - Zeng, Z.; Sun, X.; Zhang, D.; Zheng, W.; Fan, X.; He, M.; Xu, T.; Sun, L.; Wang, X.; Pan, A. (Adv. Funct. Mater., 2019)

(untitled) - Farag, A. A. M. (Opt. Laser Technol., 2007)

(untitled) - Wang, X.; Broch, K.; Scholz, R.; Schreiber, F.; Meixner, A. J.; Zhang, D. (J. Phys. Chem. Lett., 2014)

(untitled) - Lieb, M. A.; Meixner, A. J. (Opt. Express, 2001)

(untitled) - Li, B.; Gong, Y.; Hu, Z.; Brunetto, G.; Yang, Y.; Ye, G.; Zhang, Z.; Lei, S.; Jin, Z.; Bianco, E.; Zhang, X.; Wang, W.; et al. (Angew. Chem., Int. Ed., 2016)

(untitled) - Tan, Y.; Ma, L.; Gao, Z.; Chen, M.; Chen, F. (Nano Lett., 2017)

(untitled) - Jiang, N.; Foley, E. T.; Klingsporn, J. M.; Sonntag, M. D.; Valley, N. A.; Dieringer, J. A.; Seideman, T.; Schatz, G. C.; Hersam, M. C.; Van Duyne, R. P. (Nano Lett., 2012)

(untitled) - Ling, X.; Moura, L. G.; Pimenta, M. A.; Zhang, J. (J. Phys. Chem. C, 2012)

(untitled) - Padgaonkar, S.; Amsterdam, S. H.; Bergeron, H.; Su, K.; Marks, T. J.; Hersam, M. C.; Weiss, E. A. (J. Phys. Chem. C, 2019)

(untitled) - Greulich, K.; Belser, A.; Bölke, S.; Grüninger, P.; Karstens, R.; Sättele, M. S.; Ovsyannikov, R.; Giangrisostomi, E.; Basova, T. V.; Klyamer, D.; Chassé, T.; Peisert, H. (J. Phys. Chem. C, 2020)

(untitled) - Yin, Y.; Miao, P.; Zhang, Y.; Han, J.; Zhang, X.; Gong, Y.; Gu, L.; Xu, C.; Yao, T.; Xu, P.; Wang, Y.; Song, B.; et al. (Adv. Funct. Mater., 2017)

(untitled) - Dong, H.; Zhu, H.; Meng, Q.; Gong, X.; Hu, W. (Chem. Soc. Rev., 2012)

(untitled) - Tebyetekerwa, M.; Zhang, J.; Xu, Z.; Truong, T. N.; Yin, Z.; Lu, Y.; Ramakrishna, S.; Macdonald, D.; Nguyen, H. T. (ACS Nano, 2020)

(untitled) - Sahoo, P. K.; Zong, H.; Liu, J.; Xue, W.; Lai, X.; Gutiérrez, H. R.; Voronine, D. V. (Opt. Mater. Express, 2019)

(untitled) - Chen, Y.-T.; Pan, L.; Horneber, A.; van den Berg, M.; Miao, P.; Xu, P.; Adam, P.-M.; Meixner, A. J.; Zhang, D. (Nanophotonics, 2019)

(untitled) - Züchner, T.; Failla, A. V.; Meixner, A. J. (Angew. Chem., Int. Ed., 2011)